Towards Automated design of Combinational Circuits Using Evolutionary Techniques (International Journal of Engineering and Computer Science, 2013)
We introduce a technique, based on Evolutionary algorithms to automate and optimize the design of combinational circuits. Logic circuits are at the core of modern computing. The process of designing circuits which are efficient is thus of critical importance. By exploring the full range of possible solutions, circuits could be discovered which are superior to the best known human designs. Automated design techniques borrowed from artificial intelligence have allowed exactly that. Specifically, the application of genetic algorithms has allowed the creation of circuits which are substantially superior to the best known human designs. Systematic search is, perhaps, best exemplified by its simplest and most intuitive manifestation. This proposal expands on such previous research with a three-fold approach comprised of, A distinct optimizations for the application of genetic algorithms to design, the formulation and implementation of a systematic search technique to the problem and a comparison of the relative merits of the optimized genetic algorithm and the systematic search technique and the results also compared with Ant Colony Optimization (ACO) and Particle Swarm Optimization (PSO) algorithms..